Anesthesia and World War II: When the Battlefield Becomes a Research Field—A Bibliometric Analysis of the Influence of World War II on the Development of Anesthesiology. (January 2022) - Jakus, Lien; Docquier, Pierre-Louis; Veyckemans, Francis; Reding, Raymond
Abstract : At the outbreak of World War II (WWII), anesthesiology was struggling to establish itself as a medical specialty. The battlefield abruptly exposed this young specialty to the formidable challenge of mass casualties, with an urgent need to provide proper fluid resuscitation, airway management, mechanical ventilation, and analgesia to thousands. But while Europe was suffering under the Nazi boot, anesthesia was preparing to rise to the challenge posed by the impending war. While war brings death and destruction, it also opens the way to medical advances. The aim of this study is to measure the evolution of anesthesia owing to WWII. We conducted a retrospective observational bibliometric study involving a quantitative and statistical analysis of publications. The following 7 journals were selected to cover European and North American anesthesia-related publications: Anesthesia & Analgesia, the British Journal of Anaesthesia, Anesthesiology, Schmerz-Narkose-Anaesthesie, Surgery, La Presse Médicale, and The Military Surgeon (later Military Medicine ). Attention was focused on journal volumes published between 1920 and 1965. After reviewing the literature, we selected 12 keywords representing important advances in anesthesiology since 1920: "anesthesia, " "balanced anesthesia, " "barbiturates, " "d-tubocurarine, " "endotracheal intubation, " "ether, " "lidocaine, " "morphine, " "spinal anesthesia, " "thiopental, " "transfusion, " and "trichloroethylene." Titles of original articles from all selected journals editions between 1920 and 1965 were screened for the occurrence of 1 of the 12 keywords. A total of 26, 132 original article titles were screened for the occurrence of the keywords. A total of 1815 keywords were found. Whereas Anesthesia & Analgesia had the highest keyword occurrence (493 citations), Schmerz-Narkose-Anaesthesie had the lowest (38 citations). The number of publications of the 12 keywords was significantly higher in the postwar than in the prewar period (65% and 35%, respectively; P < .001). Not surprisingly, the anesthesiology journals have a higher occurrence of keywords than those journals covering other specialties. The overall occurrence of keywords also showed peaks during other major conflicts, namely the Spanish Civil War (1936–1939), the Korean War (1950–1953), and the Vietnam War (1955–1975). For the first time, this study demonstrates statistically the impact of WWII on the progress of anesthesiology. It also offers an objective record of the chronology of the major advances in anesthesiology before and after the conflict. While the war arguably helped to enhance anesthesiology as a specialty, in return anesthesiology helped to heal the wounds of war.